2021
DOI: 10.3390/molecules26103026
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Physicochemical Properties, and Structural Characteristics of Arabinoxylan from Hull-Less Barley

Abstract: Arabinoxylan (HBAX-60) was fractioned from alkaline-extracted arabinoxylan (HBAX) in the whole grain of hull-less barley (Hordeum vulgare L. var. nudum Hook. f. Poaceae) by 60% ethanol precipitation, which was studied for physicochemical properties and structure elucidation. Highly purified HBAX-60 mainly composed of arabinose (40.7%) and xylose (59.3%) was created. The methylation and NMR analysis of HBAX-60 indicated that a low-branched β-(1→4)-linked xylan backbone possessed un-substituted (1,4-linked β-Xyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Arabinose and xylose, which are the arabinoxylan fractions, accounted for 4.9% and 8.3% of BF; bgl were 20.4% and 40.4%, respectively. A previous study reported arabinose and xylose ratios of 26.3% and 38.3%, respectively, for whole-grain barley extracted with alkali [ 18 ], results which are mostly consistent with this study. Therefore, SDF of BF had a high purity of β-glucan, and bgl had high arabinoxylan.…”
Section: Resultssupporting
confidence: 93%
“…Arabinose and xylose, which are the arabinoxylan fractions, accounted for 4.9% and 8.3% of BF; bgl were 20.4% and 40.4%, respectively. A previous study reported arabinose and xylose ratios of 26.3% and 38.3%, respectively, for whole-grain barley extracted with alkali [ 18 ], results which are mostly consistent with this study. Therefore, SDF of BF had a high purity of β-glucan, and bgl had high arabinoxylan.…”
Section: Resultssupporting
confidence: 93%
“…25 There are limited studies addressing the ASF structure extracted from highland hulless barley. However, two recent studies have reported molecular weights for alkaline extracted hulless barley fiber in the range of 2.98 × 10 5 Da 8 and 2.22 × 10 5 Da, 26 in agreement with the finding of the present study.…”
Section: Molecular Weight Distributionsupporting
confidence: 94%
“…Such highly multiply-branched arabinoxylan structure have not been previously reported in the literature for hulless barley or other common cereal AXs. 8,[25][26][27] Among the arabinosyl residues, higher abundances were found in the multiple branched residues, including '→2,3,5)-Araf-(1→', '→3,5)-Araf-(1→' and '→3)-Araf-(1→', compared to the terminal units 'Araf-(1→', which suggests a complex molecular structure of AX in the ASF fiber. The presence of 5-linked arabinose branches is known to be associated with the existence of etherified ferulic acids on the fiber molecule, 27 suggesting that this ASF fiber may exhibit a high level of covalent attachment of ferulic acids, potentially leading to superior antioxidant properties.…”
Section: Glycosidic Linkage Patterns Of Wsf and Asfmentioning
confidence: 98%
“…1b, revealing a wide single peak at 3410 cm −1 which indicates the hydroxyl O‐H stretching vibration of polysaccharide. Additionally, a small band at 2922 cm −1 corresponds to the C‐H stretching and bending vibration of methyl and methylene, respectively (Yao et al ., 2021). The characteristic absorption peaks of sugar, at 1416 cm −1 and 1385 cm −1 , suggest the presence of polysaccharide components, thereby inferring the polysaccharide nature of the component (Jinxin et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This observation contrasts with the spongy network structures of AX extracted from spring wheat flour (Campa‐Mada et al ., 2013). However, it aligns with the solid morphology of AX extracted from bran‐removed barley (Yao et al ., 2021). The differences in the SEM results could potentially be attributed to variations in the pretreatment and extraction methods employed for the AX source materials.…”
Section: Resultsmentioning
confidence: 99%